Faktor Determinan Menurunnya Minat Belajar Matematika Anak Down Syndrome SDN Betet 1 Kediri (Determinants of Decreased Interest in Learning Mathematics Among Children with Down Syndrome at SDN Betet 1 Kediri) - Rika, Rismawati; Nur, Kholis (Happiness: Journal of Psychology and Islamic Science, 2025)
This study examines the determinants of decreased interest in learning mathematics among children with Down syndrome and the efforts to address this decline. The purpose of this research is to deeply analyze the factors underlying the reduced learning interest of children with Down syndrome and to identify strategies to improve their learning interest. This study employs a qualitative approach with a case study method. The research was conducted at SDN Betet 1 Kediri, an inclusive school that supports students with special needs, with three children with Down syndrome as the subjects and special education teachers and parents as the main informants. Data were collected through direct observation, structured and unstructured interviews, and documentation. Data validity was ensured through source and method triangulation. Data analysis was conducted interactively, including data collection, reduction, presentation, and conclusion drawing. The results of this study indicate two main findings. First, the factors contributing to the decline in learning interest include a lack of intrinsic motivation, fluctuating learning moods, unengaging teaching methods, and insufficient motivation from parents. Second, the efforts made by teachers and parents to address the decline in learning interest involve paying attention to the children, assisting them during learning, using engaging teaching methods, and providing materials tailored to their needs.